The seventh trumpet : a mystery of Ancient Ireland - Tremayne, Peter (Tremayne, Peter. Sister Fidelma novels., 2013)
Summoned by her brother, the king, when the body of a murdered noble is discovered near Cashel in 670 Ireland, Fidelma and her companion, Eadulf, follow scanty clues linking the victim a violent uprising under the leadership of a religious fanatic. By the author of Behold a Pale Horse.